Designing a tool-post grinder - Ahmad Zaki Yamani, Ahmad Danial (2024)
This project is about designing and fabricating a tool-post grinder, without wasting too much cost on the making of it. Even though the existing tool-post grinders have a lot of advantages, the price is too pricey. Tool post grinders are commonly used for finishing the surfaces of workpieces, with a high level of precision and smoothness achievable. The tool post grinder fabricated on this project might not be as good as the expensive one, but it can still be used for surface finishing of workpiece. When conducting this project, machining processes such as welding, cutting, and grinding are going to be applied to fabricate the product